If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + 3 = 59 Reorder the terms: 3 + 7m = 59 Solving 3 + 7m = 59 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7m = 59 + -3 Combine like terms: 3 + -3 = 0 0 + 7m = 59 + -3 7m = 59 + -3 Combine like terms: 59 + -3 = 56 7m = 56 Divide each side by '7'. m = 8 Simplifying m = 8
| sin(2x+5)=sin(x-1) | | x^3-6x^2+20x=0 | | 2x^3-6x^2+20x=0 | | x+2.5z=18 | | 27x+11y+6z=1200 | | ln(x+7)=2 | | (60-d)(40-2d)=0 | | (60-d)(40-2d)=1312.5 | | 2a+4b+8c=200 | | x^3-2x^2-7x+6=0 | | 24(x+4)=24 | | 46(x-2)=18 | | 83(n+4)=7 | | 108(n-3)=12 | | (10+15)x(2+3)= | | 85n-6=19 | | 104y-3=14 | | (10)8-x+x=3[(10)x+8-x]-16 | | 2(-y+1)=5y+2(6-y) | | 3(x+2.98)=2x | | 123x+1=21 | | 13x+9y=136 | | 13+9y=136 | | 13x=9y+136 | | 164x+17=9 | | 2x^2-12x+y+14=0 | | -5600+200m=-2800 | | -5600+200m=0 | | 1.5n+(-2+0.5)=3-2(4.5+0.5) | | 4(x+3)=37 | | 5x+4(-3x+8)=x-8 | | abs(6x^2-5x+1)=5x-6x^2-1 |